Analisis Implementasi Strategis TJSL Berbasis Sustainability Empowerment - Rahim, Putrianne Warna; Hendriyani, Chandra; Vindiazhari, Nadia Rizky (Jurnal Sekretaris dan Administrasi Bisnis, 2026)
This study aims to analyze the strategic implementation of the Social and Environmental Responsibility Program (TJSL) at PT PLN Central Java Transmission Unit (PT PLN UIT JBT) in promoting community empowerment based on sustainable development. The background of this study is based on the paradigm shift in TJSL from a charitable philanthropic approach toward a strategic approach oriented toward creating long-term value for both the company and the community. This study examines the Kampung Edukasi Wisata Peduli dan Ramah Lingkungan (KETAPANG) Program in Kebonmanis, Cilacap, as a model of community-based TJSL implementation. Using a qualitative approach with data analysis conducted using the Miles, Huberman, and Saldana interactive model, the research findings indicate that the implementation of TJSL has integrated four main pillars: social, environmental, economic, and legal and governance. Theoretically, the findings of this study align with the Triple Bottom Line concept, which emphasizes a balance between social (people), environmental (planet), and economic (profit) aspects, as well as the Creating Shared Value concept, which asserts that companies can generate economic value while simultaneously addressing social and environmental issues. Meanwhile, principles in ISO 26000 such as accountability, transparency, and stakeholder engagement have begun to be implemented, but still require strengthening in terms of impact assessment and program sustainability. This TJSL program not only has a positive impact on the community but also supports the company’s operational sustainability, particularly in maintaining the security of transmission assets and social relations with the community. However, this study also identified limitations in optimizing integration among the pillars and in measuring long-term impacts, which have not yet been fully standardized. Therefore, strengthening strategies, program innovations, and impact-based evaluation systems is necessary to ensure that TJSL implementation becomes increasingly effective, adaptive, and sustainable